(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
Wild medicinal and aromatic plants represent renewable natural resources and a valuable product for Bulgaria's export. Despite the appropriate regulatory framework, there is unregulated overharvesting of medicinal plants, such as collection of plants in non-permitted quantities and collection of plants included in prohibited lists. These illegal practices in combination with the negative anthropogenic impact, lead to a cumulative negative effect on natural habitats. In accordance with the Bulgarian strategy for sustainable use of biological resources, studying, assessment, and monitoring of the natural distribution, abundance, structure, and dynamics of the wild populations are required. In order to obtain correct quantitative data, it is necessary to carry out long-term studies, especially on the effect of overexploitation. Constantly changing demand and market trends for quantities and types of medicinal plants, as well as changing negative anthropogenic factors, requires establishment of dynamic models for rapid vulnerability assessment of wild medicinal and aromatic plants. The aim of the present study is to present and discuss some theoretical aspects of Rapid Model for Vulnerability Assessment of Medicinal Plants (RMVAMP) as well as model validation in case study of the Varna District (Noth-eastern Bulgaria). This model is based on explicit criteria and on a weighted value scheme for scoring each taxon, rather than intuitive interpretation of experts in conventional assessments. Unlike other rapid methods, which predicts vulnerability of plants to overharvesting, RMVAMP assesses more aspects and critical factors which directly affect the target medicinal species. Cumulative weighted values were incorporated in GIS environment. The natural habitats in the Varna District were categorised into classes of vulnerability and were indicated on the created map using color scale. The natural habitats of herbs that should be restricted were defined.